A prospective evaluation of cytology from biliary strictures. Issue 5 (May 1997) - Mansfield, J C; Griffin, S M; Wadehra, V; Matthewson, K
Abstract : BACKGROUND: Bile duct strictures may be benign or malignant. A definite diagnosis is desirable to advise patients of their prognosis and to identify any amenable to curative surgery. AIMS: To compare different methods of cytology sampling from biliary strictures and evaluate the use of cytology in this context. PATIENTS AND METHODS: In a prospective study 54 patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) had cytology samples obtained as follows: (1) biliary stricture brushings, (2) from the screw thread of a "Soehendra stent retriever" inserted through the stricture, (3) from the proximal end of a blocked biliary stent, and (4) cellular material spun down from a 20 ml specimen of bile. Examination of slides and rinsings was performed by an expert cytologist who graded them for the adequacy of the sample and for evidence of malignancy. RESULTS: Prolonged follow up disclosed malignancy in 52 of the 54 cases, the other two being chronic pancreatitis. Bile samples provided adequate cytology samples in 44%, the Soehendra stent retriever in 70%, retrieved stents in 84%, and cytology brush sampling in 96%. Overall, 28 malignancies were detected by cytology, including 14 of 28 pancreatic carcinomas and 12 of 16 cholangiocarcinomas. Twenty two of the malignancies were detected by brush sampling and the other methods added a total of another six cases. CONCLUSIONS: Cytology sampling is best done by brushing the biliary stricture. Cytology sampling can confirm the diagnosis in 75% of cholangiocarcinomas and 50% of pancreatic carcinomas. The techniques involved are simple to perform and should be routine clinical practice whenever potentially malignant biliary strictures are encountered at ERCP.